Reinforcement learning in repeated portfolio decisions - Linan Diao; Jörg Rieskamp (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
How do people make investment decisions when they receive outcome feedback? We examined how well the standard mean-variance model and two reinforcement models predict people's portfolio decisions. The basic reinforcement model predicts a learning process that relies solely on the portfolio's overall return, whereas the proposed extended reinforcement model also takes the risk and covariance of the investments into account. The experimental results illustrate that people reacted sensitively to different correlation structures of the investment alternatives, which was best predicted by the extended reinforcement model. The results illustrate that simple reinforcement learning is sufficient to detect correlation between investments.
Keywords: C91; D83; G11; 330; repeated portfolio decisions; reinforcement learning model; correlation; Portfolio-Management; Anlageverhalten; Betriebliche Investitionspolitik